Preparation and application of Ag plasmon Bi3O4Cl photocatalyst for removal of emerging contaminants under visible light - Long, Zeqing; Guo, Tingting; Chen, Chao; Zhang, Guangming; Zhu, Jia (Frontiers in Microbiology, 2023)
Photocatalytic degradation has been extensively investigated toward the removal emerging contaminants (ECs) from water. In this study, a series of Ag-Bi3O4Cl plasmon photocatalysts were synthesized through the photo-deposition of metallic Ag on the Bi3O4Cl surface. The effects of plasmon modification on the catalytic performance of bismuth oxychlorides were analyzed. Ag addition did not alter the morphology of Bi3O4Cl. With the increasing Ag content, the number of oxygen defects on the catalyst surface first increased and then decreased. Moreover, the surface plasmon resonance effect of Ag suppressed the recombination of electron–hole pairs, promoting the migration and separation of photocarriers and improving the light absorption efficiency. However, the addition of excessive Ag reduced the number of active sites on the Bi3O4Cl surface, hindering the catalytic degradation of pollutants. The optimal Ag-Bi3O4Cl photocatalyst (Ag ratio: 0.025; solution pH: 9; dosage: 0.8 g/L) achieved 93.8 and 94.9% removal of ciprofloxacin and tetrabromobisphenol A, respectively. The physicochemical and photoelectric properties of Ag-Bi3O4Cl were determined through various characterization techniques. This study demonstrates that introducing metallic Ag alters the electron transfer path of the catalyst, reduces the recombination rate of electron–hole pairs, and effectively improves the catalytic efficiency of Bi3O4Cl. Furthermore, the pathways of ciprofloxacin degradation products and their biotoxicity were revealed.